Legal Education in a Globalised Era: China’s Strategy for Governance and Development - Qian Hao (Public Governance, Administration and Finances Law Review)
China’s legal education plays a unique and vital role in the national strategy to modernise its legal system, a foundation that has underpinned the country’s rapid ascent. This paper analyses this often-overlooked facet of China’s development by situating legal education within the broader framework of governmental initiatives. Faced with the challenge of establishing a functional legal infrastructure with extremely limited resources, China’s policymakers have adopted two primary approaches since the late 1970s. First, they have concentrated most legislative efforts on the large-scale transplantation of Western laws. Second, they have effectively transformed law schools into hubs for generating legislative knowledge and training legal professionals. The Foreign-Related Rule of Law initiative, the latest manifestation of the state-directed strategy, continues to shape legal education by introducing new objectives and challenges. This paper argues that to fully comprehend China’s path to modernisation, one must understand how legal education is embedded within its grand national development strategy.